Choosing safe and effective anticoagulation to treat idiopathic ovarian vein thrombosis: using first principles of deep vein thrombosis management to treat a rare diagnosis: a case report and review of the literature - Erwin Yii; Hexiang Yao; Ming Yii (Journal of Medical Case Reports, 2023)
Abstract Background Ovarian vein thrombosis (OVT) often presents in the post-partum period and is associated with significant complications including inferior vena cava extension, pulmonary embolism, sepsis, and renal obstruction. Idiopathic OVT is rare, and no consensus has been agreed upon regarding its diagnosis and management. This case presents a patient who was diagnosed with idiopathic OVT and was treated with apixaban. A literature review was performed collating reported cases of idiopathic OVT to form a recommendation regarding optimal management and follow up. Case presentation A 42-year-old Chinese woman presenting with right lower quadrant pain underwent a CT abdomen after urinary tract obstruction was excluded on ultrasound. She was subsequently diagnosed with an idiopathic 35 mm ovarian vein thrombus (OVT) given no history of primary coagulopathy nor secondary aetiology. A literature review was performed collating 18 case reports with method of diagnosis and management summarized. Treatment alternatives included low molecular weight heparin, warfarin, rivaroxaban and apixaban. Most were diagnosed after work up for suspected renal calculus or appendicitis. Follow up imaging was performed from between 6 weeks to 6 months after initiation of anticoagulation. Conclusions Direct oral anticoagulants were an effective treatment for OVT, however warfarin should be commenced in those suspected of antiphospholipid syndrome awaiting confirmation or exclusion of the diagnosis.